2012
DOI: 10.3928/01477447-20111122-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Human β-defensin 3, Vancomycin, and Clindamycin on Staphylococcus aureus Biofilm Formation

Abstract: Despite improvements in surgical techniques and implant design in orthopedic surgery, implantation-associated infections are still a challenging problem for surgeons. In 2006, trace quantities of human β-defensin 3 (hBD-3) were found in human bone tissue and bone cells. Human β-defensin 3 is a 45-amino-acid peptide that is considered the most promising class of defensin antimicrobial peptides and may help in the prevention and treatment of implantation-associated infections. Studies of the effectiveness of hBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…To relate the results reported in this study to previous investigations, live/dead staining and conventional culturing were used to test antibiotic susceptibility of adherent S. sanguinis and P. gingivalis cells to demonstrate a possible correlation between the two methods regarding vitality rates in treated samples 14,34 . Both methods are commonly used in experiments on antibiotic susceptibility testing in vitro 8,16‐20 . However, poor correlation between the two methods was detected by the antibiotic susceptibility testing of adherent cells.…”
Section: Discussionmentioning
confidence: 91%
“…To relate the results reported in this study to previous investigations, live/dead staining and conventional culturing were used to test antibiotic susceptibility of adherent S. sanguinis and P. gingivalis cells to demonstrate a possible correlation between the two methods regarding vitality rates in treated samples 14,34 . Both methods are commonly used in experiments on antibiotic susceptibility testing in vitro 8,16‐20 . However, poor correlation between the two methods was detected by the antibiotic susceptibility testing of adherent cells.…”
Section: Discussionmentioning
confidence: 91%
“…Bacteria from overnight cultures were diluted 1:1000, so that 50 mL of these bacterial suspensions contained approximately 10 6 cells. Twenty-four hours before surgery, ATCC35984 and ATCC43300 cells were added to each well (tissue culture-treated polystyrene; Costar 3595; Corning Inc, Corning, NY) containing 1 mL of biofilm medium consisting of 0.5 Â BBL TSB Q3 supplemented with 0.2% (w/v) glucose (TSBG) [14,20]. Before seeding, titanium plates (1-mm-thick and 10-mm in diameter; Sh-puwei,…”
Section: Biofilm Treatmentmentioning
confidence: 99%
“…Warnke et al [13] demonstrated that the innate immune activity of HBD-3 existed inside bones, which might have potential applications in orthopedic surgery in reducing the rate of peri-implant infection. Huang et al [14] reported the role of the bactericidal effect of HBD-3 in inhibiting the formation of methicillin-susceptible S aureus biofilms. In our present study, we have proved that the bactericidal effect of HBD-3 or HBD-3 combined with UTMD and their role in inhibiting the formation of antibiotic-resistant Staphylococcus biofilms [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Activity of hBD-2 against S. aureus is present but at higher concentrations (10). hBD-3 has a stronger lethal effect on both planktonic and biofilmgrown S. aureus than vancomycin and other antibiotics at low concentrations (11,12). In another study, hBD-3 and hBD-2 were induced in patients with lesional S. aureus skin infections but not in healthy patients (13).…”
mentioning
confidence: 96%